Surviving Freedom : After the Gulag - Bardach, Janusz (Book collections on Project MUSE., 2003)
In 1941, as a Red Army soldier fighting the Nazis on the Belarussian front, Janusz Bardach was arrested, court-martialed, and sentenced to ten years of hard labor. Twenty-two years old, he had committed no crime. He was one of millions swept up in the reign of terror that Stalin perpetrated on his own people. In the critically acclaimed Man Is Wolf to Man, Bardach recounted his horrific experiences in the Kolyma labor camps in northeastern Siberia, the deadliest camps in Stalin's gulag system. In this sequel Bardach picks up the narrative in March 1946, when he was released.